2021
DOI: 10.1088/1755-1315/869/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

The condition of reef fish (family Chaetodontidae) in Krueng Raya and Ujong Pancu waters, Aceh Besar District

Abstract: This study aims to determine the condition of reef fish of the Chaetodontidae family in Krueng Raya and Ujong Pancu waters, Aceh Besar District. The study was conducted in October 2019, where six observation locations were representing the two regions. Fish observations were carried out using the Underwater Visual Census (UVC) method. The results of the study found four genera of Chaetodontidae fish consisting of 21 species. Benteng Inong Balee Station is the location with the highest number of individuals and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…Logam berat timbal (Pb) merupakan jenis logam berat yang paling dominan diteliti yaitu di 38 pelabuhan Indonesia (Gambar 3, Tabel 1). Pentingnya penelitian logam berat dapat dijadikan sebagai acuan terhadap pencegahan kerusakan yang ditimbulkan oleh logam berat yang bersifat karsenogenik baik bagi lingkungan seperti biota perairan: terumbu karang (Najmi et al, 2023), ikan karang (Fazillah et al, 2020), ikan bioindikator perairan (Octavina et al, 2021) dan makrozobenthos (Razi et al, 2021); ekosistem sekitar seperti mangrove (Octavina et al, 2022) dan lamun (Fazillah et al, 2021); dan juga dapat berdampak pada manusia dimana mengonsumsi ikan yang di daratkan di pelabuhan perikanan (Razi et al, 2022). Memperdalam informasi terkait logam berat dapat memberikan solusi alternatif mengatasi pencemaran lingkungan dari sumber daya alam baik dari tumbuhan, alga hingga bakteri serta memberikan peluang bagi teknologi dalam pengembangan dan meningkatkan efesiensi dalam perawatan lingkungan bagi masyarakat.…”
Section: Hasil Dan Pembahasan Logam Beratunclassified
“…Logam berat timbal (Pb) merupakan jenis logam berat yang paling dominan diteliti yaitu di 38 pelabuhan Indonesia (Gambar 3, Tabel 1). Pentingnya penelitian logam berat dapat dijadikan sebagai acuan terhadap pencegahan kerusakan yang ditimbulkan oleh logam berat yang bersifat karsenogenik baik bagi lingkungan seperti biota perairan: terumbu karang (Najmi et al, 2023), ikan karang (Fazillah et al, 2020), ikan bioindikator perairan (Octavina et al, 2021) dan makrozobenthos (Razi et al, 2021); ekosistem sekitar seperti mangrove (Octavina et al, 2022) dan lamun (Fazillah et al, 2021); dan juga dapat berdampak pada manusia dimana mengonsumsi ikan yang di daratkan di pelabuhan perikanan (Razi et al, 2022). Memperdalam informasi terkait logam berat dapat memberikan solusi alternatif mengatasi pencemaran lingkungan dari sumber daya alam baik dari tumbuhan, alga hingga bakteri serta memberikan peluang bagi teknologi dalam pengembangan dan meningkatkan efesiensi dalam perawatan lingkungan bagi masyarakat.…”
Section: Hasil Dan Pembahasan Logam Beratunclassified
“…However, for the province of Aceh, very little has been done and published. So far the Research on Chaetodontidae fish in Aceh that has been carried out has only been reported by [12,13], and the absence of further studies on its relationship with coral reefs. On the other hand, Aceh Province is one of the provinces in Indonesia that has coral reef resources with a fairly high associated biota [14].…”
Section: Introductionmentioning
confidence: 99%